2009
DOI: 10.1016/s0924-9338(09)70816-8
|View full text |Cite
|
Sign up to set email alerts
|

Social Cognition and General Functioning in Bipolar Disorder

Abstract: Introduction:Bipolar patients show a significant degree of psychosocial disfunction even in euthymia. Recent studies have reported deficits in Theory of Mind and emotion recognition in BD. Our hypothesis is that social cognition deficit could be associated with a poor general functioning and psychosocial disadvantage in BD.Methods:A sample of 27 euthymic bipolar patients were recluted. Based on Global Assessment of Functioning, they were divided into two groups: good or low general functioning. Euthymia was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Indeed, there is reasonable theoretical rationale for the proposition that social cognitive impairments, like neurocognitive impairments, directly influence adaptive psychosocial function in BD. Results from initial studies partly addressing social cognitive contributions in the disorder also suggest that its influence may occur in a manner that is independent from mood (Hajnal et al, 2010;Hoertnagl et al, 2011;Lahera et al, 2009;Martino et al, 2011b). Conversely, it is likely that abnormalities in emotion regulation perpetuate psychosocial dysfunction in BD by catalysing or exacerbating clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, there is reasonable theoretical rationale for the proposition that social cognitive impairments, like neurocognitive impairments, directly influence adaptive psychosocial function in BD. Results from initial studies partly addressing social cognitive contributions in the disorder also suggest that its influence may occur in a manner that is independent from mood (Hajnal et al, 2010;Hoertnagl et al, 2011;Lahera et al, 2009;Martino et al, 2011b). Conversely, it is likely that abnormalities in emotion regulation perpetuate psychosocial dysfunction in BD by catalysing or exacerbating clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is only minimal direct evidence examining the influence of these functions on outcome, the existing BD studies are preliminarily supportive of relationships between these constructs (Hajnal et al, 2010;Lahera et al, 2009;Martino et al, 2011b). That there is reasonable theoretical justification for their association, formulated on the basis of indirect support for an association between these variables from studies of related disorders and healthy populations (Kee et al, 2003;Mathews and Barch, 2010;Sparks et al, 2010), suggests that the influence of social cognition and emotion regulation on psychosocial function in BD are areas worthy of future research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies revealed that neurocognitive deficits (i.e., executive function, memory, verbal learning, attention, and processing speed) may cause perpetuating psychosocial dysfunction regardless of affective symptomatology (Baune & Malhi, 2015; Bowie et al, 2010; Burdick et al, 2010; Jaeger et al, 2007; O’Shea et al, 2010; Tabarés-Seisdedos et al, 2008; Torres et al, 2011). In addition, other studies have showed that social cognition (SC) plays an important role in psychosocial functioning in bipolar patients (Hajnal et al, 2010; Lahera et al, 2009; Martino et al, 2011; Montag et al, 2010; van Rheenen & Rossell, 2014).…”
Section: Introductionmentioning
confidence: 99%